Association of abdominal fat with serum amylase in an older cohort: The Baltimore Longitudinal Study of Aging. (June 2016) - Dias, Jenny Pena; Schrack, Jennifer A.; Shardell, Michelle D.; Egan, Josephine M.; Studenski, Stephanie
Abstract: Aims: Abdominal fat is a major determinant of metabolic diseases in older individuals. Obesity and diabetes are associated with low serum amylase (SA) levels, but the association between SA and metabolic disease is poorly understood. We investigated the association of low SA with diabetes and sex-specific associations of serum amylase with abdominal fat in older adults. Methods: In community-dwelling volunteers from the Baltimore Longitudinal Study of Aging (778 participants, age 66.8 ± 13.6 years), we assessed abdominal fat by computed tomography and diabetes status using the American Diabetes Association criteria. Linear regression analyses assessed the cross-sectional associations between abdominal fat and SA, and logistic regression assessed the odds of diabetes, given low SA. Results: In unadjusted analyses, individuals in the lowest SA quartile (<48 μ/L) had 1.97 greater odds of diabetes, (95%CI, 1.01–3.83) than those in the highest quartile (⩾80 μ/L). This association was no longer significant after adjusting for visceral adipose tissue area (VAT, dm 2 ), abdominal subcutaneous adipose tissue (SAT, dm 2 ) or BMI. In adjusted analyses, VAT and SAT were significantly associated with SA in both sexes. Among women, SA was more strongly associated with VAT than with SAT or BMI; VAT ( β = −0.117 ± 0.048, P < 0.001), SAT ( β = −0.023 ± 0.025, P = 0.346) and BMI ( β = −0.0052 ± 0.075, P = 0.49). Conclusions: The association between SA and diabetes was explained mainly by abdominal visceral fat. In women, SA was more strongly associated with VAT than with BMI or SAT. These findings provide motivation for future mechanistic studies on SA's role in metabolic diseases.